In Silico Potential of Turmeric (Cucurma longa) as Antibacterial Agent for Salmonella typhi - Boni Herdiawan; Dwi Rulitasari; Ella Triana Aprilianty; Huzaimatul Khalisah; Nur Fatichah Choirudiniyah; Jauzaa Dyah Imtiyaz; Erlix Rakhmad Purnama (BIOEDUKASI, 2018)
Indonesia is a tropical country that has a variety of endemic infectious diseases, one of these diseases is typhoid fever. Salmonella typhi is a bacterium that causes typhoid fever. Antibiotic treatment is often used but fails due to bacterial resistance to antibiotics. An alternative treatment is required to gradually substitute synthetic antibiotic. One of this potential is given by turmeric (Curcuma longa).The purpose of this research was to know the potential of turmeric as in silico antibacterial agent for Salmonella typhi using docking method. Docking result showed that the five compounds produced different values ​​on the affinity and rmsd binding parameters. The highest affinity binding value was the Ciprofloxacin compound, the lowest was Bisdemethoxycurcumin compound. The highest rmsd value was Demethoxycurcumin, while the lowest was Xanthorrhizol, and the result revealed that all compounds have bioaffinity properties. Based on the results, three compounds derived from turmeric (demethoxycurcumin, bisdemethoxy curcumin and xanthorrizol) are still not effectively used as antibacterial agent for Salmonella typhi due to the absence of equality of amino acid residues between alternative compounds turmeric with compounds which has been clinically tested as a drug and ineffective use of receptor proteins that result in less optimal alternative compounds. Keywords: Turmeric, Antibacterial, Salmonella typhi, In Silico